Redesign Tas Hand Sanitizer dari Limbah Kain Batik Cirebon - Nathya Arum; Gerardo Harisson Setianto; Sally Malinda; Widasapta Sutapa; Nida Daniyatul Muhdirah (Pradita University, 2021)
Abstract Cirebon is one of big city in Java island that develops and preserves Batik handicraft. Batik maker in Cirebon mostly producing only in primary textiles or basic clothing, while many derivative products from residual shred pieces sere less developed. Actually big portions of good residual pieces can still be used for handicrafts, especially handicraft and handmade souvenir for local and international tourists. Cirebon also the oldest batik center which influences various batik patterns at the north coast of Java Island. The research team is Interior Design students tried to solving this problem through research methods . It aim to utilize existing batik waste and develop a recycle handicraft model so that it is beneficial to the surrounding community. The research method is carried out by conducting observations, interviews and experiments online so as to produce hand sanitizer bag products. Keywords: handicraft, Cirebon batik, recycling, hand sanitizer bag